Pylons ablaze: Examining the role of 5G COVID‐19 conspiracy beliefs and support for violence - Jolley, Daniel; Paterson, Jenny L. (British journal of social psychology, 2020)
Amid increased acts of violence against telecommunication engineers and property, this pre‐registered study (N = 601 Britons) investigated the association between beliefs in 5G COVID‐19 conspiracy theories and the justification and willingness to use violence. Findings revealed that belief in 5G COVID‐19 conspiracy theories was positively correlated with state anger, which in turn, was associated with a greater justification of real‐life and hypothetical violence in response to an alleged link between 5G mobile technology and COVID‐19, alongside a greater intent to engage in similar behaviours in the future. Moreover, these associations were strongest for those highest in paranoia. Furthermore, we show that these patterns are not specific to 5G conspiratorial beliefs: General conspiracy mentality was positively associated with justification and willingness for general violence, an effect mediated by heightened state anger, especially for those most paranoid in the case of justification of violence. Such research provides novel evidence on why and when conspiracy beliefs may justify the use of violence.